(untitled) (Itinera, 2021)
Abstract: the paper considers the creative restoration of an early Christian basilica in Siponto, Apulia, realized by Italian artist Edoardo Tresoldi. Tresoldi resorts to the wire mesh as an artistic material: the restored basilica thus results in a monumental but evanescent building. After an introduction describing the public artwork, the paper will unfold in two main sections. In the first one, the focus will be on the concept of genius loci as a distinctive character of Tresoldi’s poetics. Through an Heideggerian lens, the stress will be put on the existential value of dwelling, which is highlighted by the restored church. The second section will focus on the ghostly and uncanny (unheimlich) appearance of the basilica. Thanks to authors such as Derrida and Didi-Huberman, it will be shown that a genius deloci is at work in the site as well, calling into question the different temporalities that animate the basilica. Genius loci and genius deloci will prove as a conceptual couple capable of providing us with an access to the artwork; nevertheless, they will not be understood as a dichotomy, i.e. as mutually exclusive concepts, but as opposite notions that “haunt” each other and that cannot but be used together, in the postmodernist fashion of double-coding.